Neurochemical crossroads: exploring the neurotransmitter network in chronic pain and depression comorbidity - Ma, Min; Zhang, Yue; Tao, Kunming; Lu, Zhijie (Frontiers in Molecular Neuroscience, 2025)
Chronic pain and depression often co-occur, exhibiting a complex, bidirectional relationship that significantly exacerbates the clinical burden and complicates treatment strategies. Recent studies have identified neurochemical mechanisms as the fundamental biological basis for this interaction. Specifically, the imbalance between excitatory glutamate and inhibitory γ-aminobutyric acid (GABA), dysfunction of the endogenous opioid system, and dysregulation of various neuropeptides and non-classical neurotransmitters collectively constitute the neurobiological foundation of disturbances in pain perception and emotional regulation. Glutamate-mediated synaptic excitation and the reduction of GABA’s inhibitory function contribute to central sensitization and the abnormal processing of negative emotions. The endogenous opioid system plays a critical role in alleviating pain and emotional disturbances by regulating descending pain control pathways and the limbic system, with receptor dysfunction and expression imbalance being key mechanisms in the comorbidity. Additionally, neuropeptides such as substance P, corticotropin-releasing factor (CRF), and oxytocin participate in stress responses, reward modulation, and emotional control, thereby exacerbating the pathological connection between chronic pain and depression. This review collects the most recent findings on neurochemical interactions in the comorbidity of chronic pain and depression. The goal of this summary is to further our understanding of the molecular mechanisms in this comorbidity, as well as provide theoretical support for intervening in the neurotransmitter system in a targeted way.